Hexaaquazinc(Ii) Dinitrate Bis[5-(Pyridinium-3-Yl)Tetrazol-1-Ide] - Herrera-Urbina, F; Singh, D; Enríquez-Montenegro, J; Chi-Duran, I (International Union of Crystallography, 2018)
Hexaaquazinc(II) dinitrate 5-(pyridinium-3-yl)tetrazol-1-ide, [Zn(H2 O)6](NO 3)2 ·2C6H5 N 5, crystallizes in the space group P. The asymmetric unit contains one zwitterionic 5-(pyridinium-3-yl)tetrazol-1-ide molecule, one NO3-anion and one half of a [Zn(H2 O)6]2+ cation (symmetry). The pyridinium and tetrazolide rings in the zwitterion are nearly coplanar, with a dihedral angle of 5.4 (2)°. Several O-H..N and N-H..O hydrogen-bonding interactions exist between the [Zn(H2 O)6]2+ cation and the N atoms of the tetrazolide ring, and between the nitrate anions and the N-H groups of the pyridinium ring, respectively, giving rise to a three-dimensional network. The 5-(pyridinium-3-yl)tetrazol-1-ide molecules show parallel-displaced π-π stacking interactions; the centroid-centroid distance between adjacent tetrazolide rings is 3.6298 (6) Å and that between the pyridinium and tetrazolide rings is 3.6120 (5) Å. © 2018 Chi-Duran et al.